Design of Wastewater Collection System for Bani Naim Town - Qawasmi, Anas; Abu Talib, Hammam (جامعة بوليتكنك فلسطين - مساحة, 2023)
Bani Naim Town currently lacks of a wastewater collection and treatment systems, the wastewater in the town is collected in a cesspits and wastewater trucks. This condition creates many potential health, environmental, and social risks for the town. This project presents a design for a wastewater collection system for Bani Naim Town. A comprehensive assessment of the current situation of the town and description of area as well as the detailed data and information needed for the design. This report contains the full design for a complete collection system covers all the town with main, sub-main and lateral sewers. The project also discussed the possibility of using pumps and will proposed the most suitable place for the treatment plants. The designed collection system be linked to treatment plants for recycling and use in agricultural and industrial applications.
CD, no of pages 87, مساحة 2/2023
Keywords: Designs of Wastewater Collection System